The poor belong to us : Catholic charities and American welfare - Brown, Dorothy M. (Dorothy Marie), 1932-; McKeown, Elizabeth (Harvard University Press, 1997)
Between the Civil War and World War II, Catholic charities evolved from volunteer and local origins into a centralized and professionally trained workforce that played a prominent role in the development of American welfare. Dorothy Brown and Elizabeth McKeown document the extraordinary efforts of Catholic volunteers to care for Catholic families and resist Protestant and state intrusions at the local level, and they show how these initiatives provided the foundation for the development of the largest private system of social provision in the United States.